The Effects of Using Google Sites Online Lessons with Model Creativity -Based Learning (CBL) on The topic of Organisms Basic Chemistry to analytical Skills of Grade 10 Students - Jantaratsamee , Apinya; Wutchana, Umporn (Journal of Modern Learning Development, 2023)
The aim of this research is to were 1) to compare pre- and post-learning Analytical Skills with Google Sites online lessons together with the Creativity-Based Learning (CBL) model on Organisms Basic Chemistry of Grade 10 Students and 2) To study the satisfaction of students towards Google Sites online lessons in conjunction with a creative-based learning model (CBL) on basic chemistry of living things of Grade 10 Students. The sample used in this research were 33 students in grade 10 by cluster random sampling. The tools of this research consisted of 1) Google Sites online lessons, 2) a learning management plan with a creative learning model, 3) a test for analyzing thinking skills on basic chemistry of life, and 4) a satisfaction questionnaire. of students toward online lessons, Google Sites, and creative-based learning (CBL). Statistics used for data analysis were,mean (x), standard deviation (S.D.) and hypothesis testing using dependent t-test. The following were the results: 1. after using Google Sites online lesson together with with Model Creativity -Based Learning (CBL) on The topic of Organisms Basic Chemistry Things had significantly higher analytical skills after learning than before. at level .05 2. students’ satisfaction with online lessons, Google Sites, and Creative-Based Learning (CBL) were at the highest level (x = 4.55, S.D. = 0.45).